2015
DOI: 10.1534/genetics.115.174714
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Transcription Affected by RNA Polymerase IV inZea mays

Abstract: All eukaryotes use three DNA-dependent RNA polymerases (RNAPs) to create cellular RNAs from DNA templates. Plants have additional RNAPs related to Pol II, but their evolutionary role(s) remain largely unknown. Zea mays (maize) RNA polymerase D1 (RPD1), the largest subunit of RNA polymerase IV (Pol IV), is required for normal plant development, paramutation, transcriptional repression of certain transposable elements (TEs), and transcriptional regulation of specific alleles. Here, we define the nascent transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
78
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 85 publications
11
78
1
Order By: Relevance
“…Loss of 24-nt siRNAs in rmr6-1 caused relatively low numbers of TEs to become transcriptionally de-repressed, confirming previous findings in mop1-1 and rmr6 (Jia et al, 2009;Madzima et al, 2014;Erhard et al, 2015) and supporting the hypothesis that RdDM is generally dispensable for stable silencing of the vast majority of TEs (Matzke et al, 2015). It was recently demonstrated that at RdDM loci, mop1-1 decreases DNA methylation in all C contexts but does not completely remove CHH methylation (Gent et al, 2014): lower levels of residual CHH methylation might still be sufficient to ensure DNA silencing at most RdDM loci.…”
Section: Putative Direct and Indirect Rddm Targets In Maizesupporting
confidence: 88%
See 3 more Smart Citations
“…Loss of 24-nt siRNAs in rmr6-1 caused relatively low numbers of TEs to become transcriptionally de-repressed, confirming previous findings in mop1-1 and rmr6 (Jia et al, 2009;Madzima et al, 2014;Erhard et al, 2015) and supporting the hypothesis that RdDM is generally dispensable for stable silencing of the vast majority of TEs (Matzke et al, 2015). It was recently demonstrated that at RdDM loci, mop1-1 decreases DNA methylation in all C contexts but does not completely remove CHH methylation (Gent et al, 2014): lower levels of residual CHH methylation might still be sufficient to ensure DNA silencing at most RdDM loci.…”
Section: Putative Direct and Indirect Rddm Targets In Maizesupporting
confidence: 88%
“…In addition, we found that the smaller numbers of genes that are down-regulated in the rmr6-1 background also show the same loss of gene-proximal siRNAs. Together, these data support the current model by which the geneflanking 24-nt siRNAs in maize primarily function to reinforce transcriptional silencing of TEs located near active genes, avoiding the spreading of euchromatin into the close TEs (Gent et al, 2013(Gent et al, , 2014Erhard et al, 2015;Li et al, 2015). The similar occupancy of RMR6-dependent, gene-flanking, 24-nt siRNA loci found for protein-coding genes and lncRNAs suggests that the CHH island system of RdDM is engaged near active genes independently of their coding or noncoding nature.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Msupporting
confidence: 79%
See 2 more Smart Citations
“…Recent results show that maize Pol IV also has more general effects on gene regulation, possibly unrelated to RdDM (Erhard et al, 2015). Loss of RPD1 function results in strong developmental defects, possibly explained by the ectopic expression of specific genes (Parkinson et al, 2007;Erhard et al, 2013Erhard et al, , 2015.…”
Section: Diverse Roles For Multiple Dna-dependent Rna Polymerasesmentioning
confidence: 99%